2019
DOI: 10.3390/nu11102444
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Effects of Polymerized Anthocyanin from Grape Skin on Benign Prostatic Hyperplasia

Abstract: Benign prostatic hyperplasia (BPH) is a common chronic disease of the urinary system among elderly men. Especially, the metabolic imbalance of androgen in elderly men is one of the leading causes of BPH. Dihydrotestosterone (DHT) and converted testosterone by 5-α reductase type 2 (5AR2), binding with androgen receptor (AR), affect prostate proliferation and growth. In BPH, levels of androgen signaling-related protein expression are shown highly. Androgen signaling induces the overexpression of prostate-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 34 publications
(33 reference statements)
0
25
0
1
Order By: Relevance
“…We analyzed the metabolites of MR and found that they contained a large amount of flavonoids (Figures 2 and 3). Based on previous studies showing that flavonoids have an effect on BPH [25], in this study, MRs were measured for their inhibition activity of PSA on LNCaP cells, and Igsu showed the highest activity among the eight varieties. Furthermore, the anti-prostate hypertrophy effect of Igsu was verified using the TP-induced BPH rat model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We analyzed the metabolites of MR and found that they contained a large amount of flavonoids (Figures 2 and 3). Based on previous studies showing that flavonoids have an effect on BPH [25], in this study, MRs were measured for their inhibition activity of PSA on LNCaP cells, and Igsu showed the highest activity among the eight varieties. Furthermore, the anti-prostate hypertrophy effect of Igsu was verified using the TP-induced BPH rat model.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the previous studies are very similar to our study, which may be due to the large amounts of flavonoids, polyphenols, and plant sterols found in natural foods. Phytochemicals in natural plants were recently reported to be effective in BPH [25,[34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this study demonstrated that the frequency of apoptotic cells in the anthocyanin group was significantly higher than that in BPH group [ 88 ]. Though this study did not present any information regarding the molecular mechanisms of anthocyanin-induced apoptosis in BPH, another study showed that the downregulation of Bcl-2 expression and the upregulation of Bcl-2-asscoaited X protein (Bax) expression in BPH tissues were closely associated with such pro-apoptotic activity [ 89 ].…”
Section: Management Of Benign Prostate Hyperplasia With Polyphenolmentioning
confidence: 99%
“…A study using a rat model with testosterone propionate-induced BPH also showed that the oral administration of anthocyanin (100 mg/kg) led to a significant decrease in prostate weight ( p < 0.01) ([ 89 ]. In this study, in addition to apoptosis, cell proliferation and cell cycle regulation were reported to be related to the anti-growth effects of anthocyanin in a rat BPH model [ 89 ].…”
Section: Management Of Benign Prostate Hyperplasia With Polyphenolmentioning
confidence: 99%
See 1 more Smart Citation